Peningkatan Kinerja Tenaga Pendidik dan Kependidikan Melalui Komunikasi Interpersonal Kepala Madrasah Pada Lembaga Pendidikan di Kabupaten Ponorogo - Abdul Kholiq; Nurul Hidayah (Southeast Asian Journal of Islamic Education Management, 2024)
Performance results from an individual's work in executing specific tasks. The performance of teaching and education personnel in educational institutions needs to be enhanced to achieve the institution's objectives optimally. One factor that can improve performance is the principal's interpersonal communication. This study aims to describe and analyze: (1) the application of interpersonal communication by madrasah principals; (2) the supporting and inhibiting factors for the application of interpersonal communication by madrasah principals; and (3) the role of interpersonal communication by madrasah principals in improving the performance of teaching and education personnel. This research uses a case study approach with qualitative methods, employing data collection techniques such as observation, interviews, and documentation. The results indicate that (1) the interpersonal communication of madrasah principals in relation to teaching and education personnel's performance is implemented through aspects of openness, encouragement, empathy, expressiveness, and equality; (2) well-designed and easily understandable messages, along with communicants' sufficient cognitive maturity, are supporting factors, while physical and semantic barriers are inhibiting factors; and (3) in enhancing the performance of teaching and education personnel, the interpersonal communication of the madrasah principal serves as both a controller and a source of work motivation.